Effect Of Suvarna Bhasma (Gold Calx) On Reproductive System Of Male Albino Rats: Life Sciences-Ayurveda - Godatwar P; Prasad Bs; Skandhan Kp; Mehra Bl; Singh G; Mounika B (International Journal of Life Science and Pharma Research, 2022)
“Suvarna Bhasma” (gold calx) (SB) prepared as per Ayurveda, a practicing medical system, is prescribed as a medicine in several ailments including conditions like oligozoospermia and asthenoszoospermia in male infertility. SB is prepared from pure metal gold by one of the processing methods detailed in Ayurveda classics. Gold along with other elements was reported in normal human seminal plasma. . In human pathological semen samples, the level of gold was less than normal. Gold may have a role in physiological activity of sperm as shown in case of other elements. The present study supports the hypothesis that the presence of gold is essential for sperm motility. Here we studied the effect of SB on male reproductive organs and semen from epididymis of rat. Present study was performed using Charles foster strain albino rats. Rats were divided into two groups of ten each namely, Group 1 (control) and Group 2 (study). Animals in study group were orally given a fixed amount of SB for 15 days. At the end of the study treated animals showed increase in body weight (<0.05) and testicular weight. In treated animals total sperm count (<0.05) and percentage of sperm motility were increased in epididymal fluid. Histological study showed increase in interstitial area of testes (<0.001), proliferation and branching of the epithelial layer of seminal vesicle. In the Study (gold treated) Group, the increased gold level in genital system may be responsible for the increase in sperm production and motility.